Analysing the effectiveness of online digital audio software and offline audio studios in fostering Chinese folk music composition skills in music education. - Lei, Xiaowei (Journal of Computer Assisted Learning, 2024)
Background: This research aimed at investigating the effectiveness of online digital audio software Logic Pro X and offline audio studios in creating an original folk‐style track. The goal was to define the more effective method for the perspective and quality of musical compositions that students create during learning. Objectives: This research enrolled 207 students from Hubei Polytechnic University, who were randomised to the control and experimental groups. Methods: Within one month, each participant created a folk song using software or an offline university studio, where sound editing and processing programmes were not employed. The author's questionnaire Scale of perspective and expert evaluation were used as metric methods. Results and Conclusions: The data obtained showed that both methods do not differ both in terms of perspective and in terms of the overall quality of the created tracks (p ≥ 0.05). As quality criteria, the experts considered such scales as pitch accuracy, rhythmic accuracy, tone quality and expression, articulation, dynamics, interpretation, phrasing, creativity, arrangement, and overall performance. This research showed that online digital audio software can be an effective tool in music education, just like offline studios, in terms of skill development and practice. Lay Description: Object: This study was designed to compare the effectiveness of online digital audio software Logic Pro X and a university offline audio studio in terms of the perspective and quality of the created tracks.Results: The empirical results indicated that there was no significant difference between the two groups in either perspectives or expert assessments (p ≥ 0.05). These findings can help design appropriate music curricula and integrate digital technologies into music education.Practical implications: The findings have practical implications for music teachers and educational institutions in China and other countries; they also provide scientific evidence to support the use of digital technologies in music education.